1998
DOI: 10.1042/bj3300001
|View full text |Cite
|
Sign up to set email alerts
|

Novel evidence for an ecto-phospholipid methyltransferase in isolated rat hepatocytes

Abstract: Phospholipids of isolated rat hepatocytes were labelled by preincubation with either 2 µM [methyl-"%C]S-adenosylmethionine (AdoMet) or 2 µM [methyl-"%C]methionine. Subsequent addition of phospholipase C to the suspension removed 95 % of the radioactivity from phospholipids methylated by [methyl-"%C]AdoMet within a few minutes, but was without effect on phospholipids methylated by [methyl-"%C]methionine radioactivity from the latter could, nevertheless, be removed by phospholipase C after permeabilization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, oxidative damage to sulphydril protein groups resulting from the free radical formation in CyA-treated rats could give place to loss of catalytic functions and increased degradation of proteins (Wolf et al, 1997), and both factors may lead to alteration in membrane-bound enzyme activities such as transporter proteins (Vendemiale et al, 1999). When SAMe is administered, its methyl groups are incorporated into the membrane phospholipids (Bontemps and Van Den Berghe, 1998) and this normalizes membrane fluidity and the Na + pump (Fricker et al, 1988). Additionally, it has been shown that SAMe, by normalizing methylation reactions or maintaining a high methionine pool, is able to increase protein synthesis and to stimulate methylation of membrane proteins (Mato et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative damage to sulphydril protein groups resulting from the free radical formation in CyA-treated rats could give place to loss of catalytic functions and increased degradation of proteins (Wolf et al, 1997), and both factors may lead to alteration in membrane-bound enzyme activities such as transporter proteins (Vendemiale et al, 1999). When SAMe is administered, its methyl groups are incorporated into the membrane phospholipids (Bontemps and Van Den Berghe, 1998) and this normalizes membrane fluidity and the Na + pump (Fricker et al, 1988). Additionally, it has been shown that SAMe, by normalizing methylation reactions or maintaining a high methionine pool, is able to increase protein synthesis and to stimulate methylation of membrane proteins (Mato et al, 1997).…”
Section: Discussionmentioning
confidence: 99%